Hubungan Kompetensi Pedagogik Dengan Kompetensi IPA Mahasiswa Pendidikan Guru Sekolah Dasar: Relationship of Pedagogical Competence and Science Competency of Elementary School Teacher Education - Asrial, Asrial; Zakariyya, Syahrial; Kurniawan, Dwi Agus; Septiasari, Retno (Pedagogia : Jurnal Pendidikan, 2019)
This study has the purpose of (1) How is the pedagogic competence of students of elementary school teacher education; (2) How is the science competency of elementary school teacher education students; (3) Is there a relationship between pedagogic competence and science competence of elementary school teacher education students. The research method used in this study was a quantitative survey. Based on the results of the study, students' data obtained from elementary school teacher education for pedagogic competence and science competency fall into the unfavorable category with a pedagogic percentage of 67.9% and IPA of 63.52% and obtained data for the meaning of pedagogic efficiency (7.632), min 2.0), max (13.0) and standard deviation (2.2921) while for science competencies, the average (7.84), min (0), max (16) and standard deviation (2,773) and also between pedagogic competencies with natural science competencies produce 0,483 These figures reflect the variables of pedagogic competence with science competence because the value of r is below 0.5. Pedagogic competence with IPA competency obtained probability = 0,000 <0,005, so there is a significant existence. Instead of offering a pedagogic with IPA competencies mark '*'. Means together with pedagogic competencies with IPA competencies have a significant relationship.